Pendidikan Kesehatan Dan Pendampingan Tentang Ketergantungan Psikologis Masyarakat Terhadap Platform Media Sosial Di Kabupaten Jember - Budiman, M.Elyas Arif; Yuhbaba, Zidni Nuris; Erdah Suswati, Wahyi Sholehah (PPPM Stikes Banyuwangi, 2023)
Social media users are more likely to report poor mental health. Spending too much time on social media can have a negative effect on mood and the negative impact social media can have on depression and anxiety. Public problems with social media platforms can be prevented through health education and health education. The purpose of community service is to increase knowledge about the impact of dependence on social media platforms. Preparation for implementation begins with a preliminary study related to the currently developing phenomenon and is continued with coordination with the national unitary body and coordination with the area that will be used as a place for community service activities. Community service activities are packaged to facilitate the community to be able to access mental health services and the public to know about the importance of mental health impacts due to inappropriate use of social media. The results of the pretest of public knowledge about the impact of support on social media platforms are in the category of bad knowledge of 52% and good knowledge of 48%. The results of the posttest of community service activities, the level of community knowledge increased, namely good knowledge by 62% and bad knowledge by 38%. The existence of social media which has become a medium that greatly affects human life, especially has an impact on psychological status and behavior. Poor social media users reported worse mental health, including symptoms of anxiety and depression.